2008
DOI: 10.4067/s0717-95022008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Rolling and Tongue Folding Traits in an African Population

Abstract: ODOKUMA, E. I.; EGHWORO , O.; AVWIORO, G. & AGBEDIA, U. Tongue rolling and tongue folding traits in an African population. Int. J. Morphol., 26(3):533-535, 2008.SUMMARY: Genetic variations that occur in humans are usually as a result of a plethora of factors which are of enormous value from physical anthropological window especially in studying population variation and human diversity. This study was conducted amongst unrelated volunteer students of Delta State University, Nigeria who were all of Urhobo tribe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…Chi-squared analysis of variance showed there is a significant difference (P<0.05) between those who could roll and fold their tongue and those who cannot. The findings above are similar to the study of Alfred (Sturtevant, 1940;Bulliyya, 2003;Odokuma et al, 2008;Maishnam, 2012). When males were compared with females, a higher percentage (71.0%) were folders as compared to (66.1%) female folders.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Chi-squared analysis of variance showed there is a significant difference (P<0.05) between those who could roll and fold their tongue and those who cannot. The findings above are similar to the study of Alfred (Sturtevant, 1940;Bulliyya, 2003;Odokuma et al, 2008;Maishnam, 2012). When males were compared with females, a higher percentage (71.0%) were folders as compared to (66.1%) female folders.…”
Section: Resultssupporting
confidence: 90%
“…Odokuma et al, also observed a higher incidence of rollers and folder among the Urhobo people of Nigeria (Odokuma et al, 2008). Maishnam reported higher percentage of rollers and folders in six different type tribes of Manipur, India (Maishnam, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…We are aware of only one study carried out in Southsouth Nigeria by Odokuma et al (2008) which focused on the incidence of these traits with respect to sex. The aim of the study was to determine the frequency distribution of tongue rollers and tongue folders among the Yoruba tribe of Southwestern Nigeria with a view to determining if there was any association between the ability to roll and fold the tongue.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Martin (25) reported that there was no proof for a genetic base of tongue rolling. In a more recent study, it was emphasized that tongue rolling is likely to be product of autosomal genes (26). Our result indicated that there was no significant relationship between tongue rolling ability and other investigated parameters (Table 3).…”
Section: Discussionmentioning
confidence: 45%